2018
DOI: 10.1097/md.0000000000012707
|View full text |Cite
|
Sign up to set email alerts
|

No associations exists between red blood cell distribution width and serum uric acid in both sexes

Abstract: The aim of this study was to determine whether there was a significant association between red blood cell distribution width (RDW) and uric acid (UA) in a large Chinese population.This was a cross-sectional study with an enrollment of 80,298 ostensibly healthy participants (48,971 males, 31,327 females) during the period from 2011 to 2015. In the study, database was grouped by sex and the association between RDW and UA was analyzed by quartiles of RDW.UA values between different sexes and RDW subgroups were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Concurrently, SUA levels reported in this study were lower than those reported in recent largescale studies in Japan (6.0 ± 1.4 and 4.5 ± 1.1 mg/dL in men and women, respectively) [19] and China (6.23 ± 1.38 and 4.38 ± 1.11 mg/dL in men and women, respectively) [20]. A study based in the United States reported that the mean SUA level was 4.4 mg/dL in white women; 4.9 mg/ dL in black women; 5.8 mg/dL in white men; and 6.0 mg/ dL in black men [21]. Therefore, the average SUA level may differ according to sex, race, and place of residence.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, SUA levels reported in this study were lower than those reported in recent largescale studies in Japan (6.0 ± 1.4 and 4.5 ± 1.1 mg/dL in men and women, respectively) [19] and China (6.23 ± 1.38 and 4.38 ± 1.11 mg/dL in men and women, respectively) [20]. A study based in the United States reported that the mean SUA level was 4.4 mg/dL in white women; 4.9 mg/ dL in black women; 5.8 mg/dL in white men; and 6.0 mg/ dL in black men [21]. Therefore, the average SUA level may differ according to sex, race, and place of residence.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this finding, another study showed that there was no association between RDW in either sex. 57 Conversely to this finding, a larger RDW was associated with a higher risk of morbidity in males compared to females. 37 On the other hand, a study has shown that women have a statistically significantly higher RDW value compared to men.…”
Section: Discussionmentioning
confidence: 75%
“… 56 A study demonstrated no association existed between RDW and sex in either gender. 57 Several genetic risks were previously associated with different traits and diseases and found that most of these, especially those related to cholesterol (both LDL and HDL), triglycerides, systolic blood pressure, BMI, diabetes, and some inflammatory diseases were significantly associated with RDW. 58 However, the importance of RDW scores in screening, diagnosis, and progression of ESRD has not been well researched.…”
Section: Introductionmentioning
confidence: 99%
“…We used data from a cross‐sectional, community‐based health‐check investigation in Tianjin Medical University General Hospital. The rational and methodology have been reported previously . In brief, a questionnaire was self‐reported by the ostensible healthy participants, who came to our institution for the annual medical checkup.…”
Section: Methodsmentioning
confidence: 99%